Hubungan Pengetahuan dengan Perilaku Pencegahan Penyakit Menular Seksual (PMS) melalui Penggunaan Kondom pada Pekerja Seks Komersial (PSK) di Wilayah Mangga Besar Jakarta Pusat Tahun 2014 - Edward Syam (Majalah Sainstekes, 2017)
PSK is is one of the most vulnerable groups are infected with sexually transmitted diseases (STDS). The Mangga Besar of Central Jakarta  is a spread of PSK and place a night club which allows the occurrence of free sex behaviour and   ultimately at   risk against STDS.  The   purpose   of this research is to know the relationship of knowledge with the behavior prevention of STDS on commercial sex workers (PSK) in The Mangga Besar of  Central  Jakarta  in  2014. The  method  in  this  research is a survey that uses Cross-sectional method. The subjects in the research were 253 workers of   commercial   sex   in   The   Mangga   Besar   of   Central   Jakarta. Data analysis use Chi Square test. The results of the research is known significant (p value 0.011 and OR value 3.736) 60.7% of commercial sex workers who perform preventive  of  STDS  as  well.  This  study is health counselling about PMS, increasing confidence the PSK,   post   messages about health prevention of STDS, and support health workers against commercial sex workers.